Exclusive Rights Stimulate Design Around: How Circumventing Edison's Lamp Patent Promoted Competition and New Technology Development. (9th August 2021) - Katznelson, Ron D; Howells, John
ABSTRACT: Designing around patents is prevalent but not often appreciated as a means by which patents promote economic development through competition. We provide a novel empirical study of the extent and timing of designing around patent claims. We study the filing rate of incandescent lamp-related patents during 1878–1898 and find that the enforcement of Edison's incandescent lamp patent in 1891–1894 stimulated a surge of patenting. We studied the specific design features of the lamps described in these lamp patents and compared them with Edison's claimed invention to create a count of noninfringing designs by filing date. Most of these noninfringing designs circumvented Edison's patent claims by creating substitute technologies to enable participation in the market. Our forward citation analysis of these patents shows that some had introduced pioneering prior art for new fields. This indicates that invention around patents is not duplicative research and contributes to dynamic economic efficiency. We show that the Edison lamp patent did not suppress advance in electric lighting and the market power of the Edison patent owner weakened during this patent's enforcement. We propose that investigation of the effects of design around patents is essential for establishing the degree of market power conferred by patents. JEL : D21 - Firm Behavior: Theory, D22 - Firm Behavior: Empirical Analysis, K11 - Property Law, K21 - Antitrust Law, L12 - Monopoly; Monopolization Strategies, N8 - Micro-Business History, O31 - Innovation and Invention: Processes and Incentives, O32 - Management of Technological Innovation and R&D, O33 - Technological Change: Choices and Consequences, O34 - Intellectual Property and Intellectual Capital